Experimental Assessment of Water Sprays Utilization for Controlling Hydrogen Sulfide Releases in Confined Space - Dongfeng Zhao; Chao Li; Jun Liu; Guoying Zhou; Qingdong Zhang; Chunshuang Liu (Journal of Nanotechnology)
This paper reported the utilization of water spray for controlling H2S release in a confined space, which is especially important in industry. A typical spray tower was modified to simulate the confined space for people's enterable routine operation (e.g., pump room), in which the dilution capacity of water sprays can also be evaluated. This work consists of two parts: the first part focuses on the influences of different operating conditions on chemical dilution capacities of water sprays in mechanisms; the second one is comparison between two nozzle configurations for evaluating their feasibilities of practical application. Water sprays express eligible performance for H2S release control even though their dilution capacity was weakened at high gaseous concentrations and rates of releases. The presence of Na2CO3 can significantly improve absorption effectiveness of H2S in water and the optimal Na2CO3 additive was found to be 1.0 g·L−1 in this test. Compared with Na2CO3, adjusting water flow rate may be an effective strategy in enhancing dilution capacity of water sprays due to the fact that larger flow rate led to both less dilution time (TD) and dilution concentration (CD). Furthermore, multinozzle configuration is more efficient than single-nozzle configuration under the same water consumption.